Mortality Comparison in Men and Women after Treatment of Myocardial Infarction at Tertiary Care Hospital (Medical Forum Monthly, 2024)
Objective: The objective of this study was to determine the 30 days mortality comparison in men and women after treatment of MI.Study Design: Observational / descriptive study.Place and Duration of Study: This study was conducted at the Department of Cardiology, Liaquat University Hospital Hyderabad from September 2015 to February 2016.Materials and Methods: All the cases diagnosed of STEMI and NSTEMI, both genders and age between 25 to 85 years incorporated in this study.30 days mortality of patients was recorded at hospital or through contacts numbers of deceased’s close relatives.Results: The mean age of the cases was of 56 ± 12.2 years. Males were in the majority as compare to females 129 (69%) and 57 (31%) respectively. 43(23.4%) patients out of total 186 died within 30 days after acute myocardial infarction. On the gender wise comparison females mortality 21 (36.8%) was significantly high in the comparison of males 22 (17.05%) after treatment of myocardial infarction. P-value 0.001.Conclusion: This study established that mortality higher in patient with acute myocardial infarction. Mortality was significantly elevated in females as contrasted to males.